1970
DOI: 10.1007/bf01211885
|View full text |Cite
|
Sign up to set email alerts
|

Observations on the effect of a ganglion blocking agent on responses to intravenous glucose infusion

Abstract: Plasma-Cortisolspiegel zeigten bei dieser Art der Glucose-Verabreichung eine fallende Tendenz.-Die Befunde stimmen iiberein mit der Annahme einer dauernd wirksamen nervalen Steuerung der Glueose-IIomSostase bei Normalpersonen und mib der MSglichkeit, da2 einige der Friiherscheinangen des Diabetes auf einer StSrung dieser Steuerungsmechanismen beruhen.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
0

Year Published

1970
1970
2009
2009

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 33 publications
2
3
0
Order By: Relevance
“…Finally, the above studies provide support for the suggestion that the anomalies observed in insulin release in some diabetics (54)(55)(56) could be related to anomalous or absent autonomic modification of B-cell function (31,42,57). The anomalies include: a quantitative reduction in the amount of insulin released in response to glucose challenge (54) in some, but not all, (58) diabetics with retention of apparently normal responsiveness to theophyllin (59) and glucagon (60), and a "delay" in insulin release in response to glucose challenge (54)(55)(56)61).…”
Section: Discussionsupporting
confidence: 57%
“…Finally, the above studies provide support for the suggestion that the anomalies observed in insulin release in some diabetics (54)(55)(56) could be related to anomalous or absent autonomic modification of B-cell function (31,42,57). The anomalies include: a quantitative reduction in the amount of insulin released in response to glucose challenge (54) in some, but not all, (58) diabetics with retention of apparently normal responsiveness to theophyllin (59) and glucagon (60), and a "delay" in insulin release in response to glucose challenge (54)(55)(56)61).…”
Section: Discussionsupporting
confidence: 57%
“…Our results are contradictory to those published by Rayis and Bethune (1970) showing a fall in plasma ACTH to undetectable levels 10-20 minutes after intravenous glucose load or 30 minutes after oral administration. In the same way Bllrr, Hudson, Page and Taft (1970) have observed in a few subjects a fall in plasma cortisol after intravenous glucose load. But owing to the half life of plasma cortisol their results are compatible with an abrupt stop in cortisol secretion therefore ACTH one, phenomen on we did not observe.…”
Section: Discussionsupporting
confidence: 68%
“…Possible reasons for such an anomaly in our preparation might result from changes in the basal metabolic state and the reactivity of insulin release mechanisms of pancreatic P-cells obtained from animals fasted overnight and isolated from all other tonic or facilitating influences originating elsewhere in the organism, such as humoral regulators of gastrointestinal origin (33,34,(38)(39)(40)(41), hormones originating in other endocrine glands (15,42,43), and the autonomic nervous system (28, [44][45][46][47][48][49][50][51][52]. The absence of such factors may result in failure to maintain critical concentrations of cAMP or of other as yet hypothetical cofactors required for full effectiveness of substrate stimulation.…”
Section: Resultsmentioning
confidence: 99%